Epidemiology of gastric cancer and risk factors - Cavatorta, Ottavia; Scida, Serena; Miraglia, Chiara; Barchi, Alberto; Nouvenne, Antonio; Leandro, Gioacchino; Meschi, Tiziana; de' Angelis, Gian Luigi; Di Mario, Francesco (Acta Biomedica Atenei Parmensis, 2018)
Gastric cancer is, still nowadays, an important healthcare problem worldwide. In Italy, it represents the fifth tumour by frequency in both men and women over 70 years old. A crucial point is represented by the percentage of early gastric cancers usually found, which is actually very low, and it carries to a worse morbidity and mortality. The most important focus in this oncological disease, is to perform an effective detection of the most common precancerous lesion linked with this neoplasia, chronic atrophic gastritis, in order to avoid the future outcome of gastric cancer itself.